2009
DOI: 10.1103/physrevlett.103.057205
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Induced Critical Behavior of Ferromagnetic Phase Transition in Sm-Nd-Sr Manganites

Abstract: We report on the hydrostatic pressure dependence of the order of ferromagnetic (FM) to paramagnetic (PM) phase transition in a (Sm(0.7)Nd(0.3))(0.52)Sr(0.48)MnO(3) single crystal. At ambient pressure, the system undergoes a first-order FM-PM phase transition at 146 K. The application of pressure increases the T(C), suppresses the hysteresis width, and thus makes the transition second order. We have analyzed the critical behavior associated with the second-order FM-PM transition in the presence of an external p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 23 publications
1
21
1
Order By: Relevance
“…Therefore, it can be proposed that it is the formation of ferromagnetic clusters that leads to a percolation mechanism for conduction and metallic behaviors observed at T > T C in the paramagnetic region for the x = 0.2 and 0.25 samples [55,69]. A recent study has shown that the PM-FM transition of a (Sm 0.7 Nd 0.3 ) 0.52 Sr 0.48 MnO 3 manganite transforms from a FOMT to a SOMT when subjected to an external pressure [58]. The critical exponents of this sample (ˇ= 0.358, = 1.297) under external pressure are close to those expected for the 3D Heisenberg model (ˇ= 0.365, = 1.336).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, it can be proposed that it is the formation of ferromagnetic clusters that leads to a percolation mechanism for conduction and metallic behaviors observed at T > T C in the paramagnetic region for the x = 0.2 and 0.25 samples [55,69]. A recent study has shown that the PM-FM transition of a (Sm 0.7 Nd 0.3 ) 0.52 Sr 0.48 MnO 3 manganite transforms from a FOMT to a SOMT when subjected to an external pressure [58]. The critical exponents of this sample (ˇ= 0.358, = 1.297) under external pressure are close to those expected for the 3D Heisenberg model (ˇ= 0.365, = 1.336).…”
Section: Resultsmentioning
confidence: 95%
“…Above the critical point (x > 0.1), the system shows a SOMT with the critical exponents belonging to the Heisenberg universality class. The change in nature of the PM-FM transition with chemical (internal) pressure (Sr doping) clearly points to a strong coupling between the magnetic order parameter and lattice strain in these doped manganites [58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coexistence of contrasting orders of almost similar energies and their tunablity with various parameters is considered to be responsible for the observed physical properties 4,5 . The pressure-dependent behaviour of manganites close to half-doping, is being studied currently 6,7 . However, these studies have been on samples that are close to, but below, half-doping and accordingly have ferromagnetic (FM) ground-state that is obtained directly from the high-temperature paramagnetic (PM) phase through a first order phase transition.…”
Section: Pacs Numbers:mentioning
confidence: 99%
“…As PSCMO4 sample is close to metalinsulator phase boundary, the effect of hydrostatic pressure on magnetic transition can be significant as in the case of other perovskite manganites with ferromagnetic ground state. [15][16][17][18][19][20][21][22][23][24] In conclusion, we have investigated the effect of hydrostatic pressure and magnetic field on magnetic, CO-OO, and structural transitions for Pr(Sr 1Àx Ca x ) 2 Mn 2 O 7 (x ¼ 0.4 and 0.9). At low field, both the systems are magnetically highly anisotropic but the anisotropy decreases systematically with the increase of H. For x ¼ 0.4 sample, CO-OO transition is insensitive to both H and P, while the antiferromagnetic transition shifts towards higher temperature with the increase of P. For x ¼ 0.9 sample, with the increase of P, though the high-temperature CO-OO transition does not get affected significantly, the low-temperature CO-OO transition decreases rapidly.…”
Section: 3mentioning
confidence: 97%